Modern Methods of Studying the Problem of Benign Vascular Lesions of The Nasal Cavity: Methods of Assessment and Study of Influencing Factors - Lutfullayev G.U.; Nematov U.S.; Khamraev F. H. (Zien Journals, 2024)
Vascular tumors make up 1-7% of benign neoplasms in humans. 60-80% of these tumors are located in the head. In childhood tumors, their development is more often associated with developmental anomalies or the presence of undifferentiated embryonic remnants in the child's body, which have a greater capacity for growth. In the early stages of development, benign neoplasms in the nasal cavity, paranasal sinuses, and nasopharynx usually manifest with minor nonspecific symptoms, which are often overlooked by both patients and doctors. Therefore, early diagnosis of benign tumors in these locations is of paramount importance
Keywords: benign neoplasms of the nasal cavity; paranasal sinuses and nasopharynx; diagnosis